The role of clinical diagnostic criteria for anti-N-methyl-D-aspartate receptor encephalitis in children: A case report - Irawan Mangunatmadja; Ricca Fauziyah; Achmad Rafli (Paediatrica Indonesiana, 2022)
Encephalitis is a neurological disorder that develops rapidly into a progressive encephalopathy caused by inflammatory processes in the brain. The incidence of encephalitis in developed countries is 5-10 per 100,000 per year. Encephalitis can affect all ages and cause long-term effects on patients, their families, and society.1-3 Autoimmune encephalitis, including anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis, is increasingly recognized as a cause of encephalitis in children and has a considerable mortality rate of 5-7%.4 Physicians should suspect anti-NMDAR encephalitis in patients with prominent neuropsychiatric symptoms and movement disorder.1-3 We report here a case of anti-NMDAR encephalitis and discuss the role of clinical criteria in diagnosing anti-NMDAR encephalitis in children.